Analisis Integratif Valuasi Ekonomi Lingkungan Pada Hutan, Laut, Dan Kota Yang Berkelanjutan - Nur Fadhli, Ahmad; Syahrial Maulana (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
Rapid economic development in Indonesia has driven ecological transformation across forests, marine areas, and urban spaces, yet it has also placed serious pressure on environmental carrying capacity. The imbalance between economic activity and natural resource sustainability calls for an integrated approach to assess the economic value of environmental services comprehensively. This article is a literature review that examines the concepts and applications of environmental economic valuation within three main ecological domains—forests, oceans, and cities—drawing on empirical studies and national policy frameworks. Approaches such as the Total Economic Value (TEV), Contingent Valuation Method (CVM), and Travel Cost Method (TCM) are utilized to estimate both direct and indirect benefits that ecosystems contribute to human welfare. The findings reveal that forests significantly support climate change mitigation and local economies through ecosystem services; marine ecosystems generate high economic value via fisheries and blue carbon; while urban areas present valuation challenges due to pollution and the degradation of open spaces. This review emphasizes the importance of integrating cross-ecosystem economic valuation as a foundation for green fiscal policy and sustainable development strategies that balance economic growth with environmental conservation